Integration of Multicultural Education Values in Learning Pancasila and Citizenship Education in Catholic High Schools Saint Andrew Palu - Novlita Engyuluis Ambedale; Jamaluddin; Juraid Abdul Latief (Kirana Publisher (KNPub), 2023)
The integration of multicultural educational values is an effort to combine learning strategies that include multicultural educational values in accepting and affirming human differences and similarities that include diversity, race, language, religion, ethnicity, and gender. This study aims to find out how to plan, implement and evaluate the integration of multicultural education values in learning Pancasila and Citizenship Education at Santo Andreas Palu Catholic High School, specifically in Classes XA and XB. The research method used is qualitative research. The collection of data that has been used is observation, interviews, and documentation. The research subjects are teachers, students, and school principals. Data analysis uses a descriptive model through data reduction, data presentation, and conclusions. The results of the study show: 1) The teacher does the planning by first making a lesson plan (RPP) in which the values of multicultural education include inclusive values, tolerance, mutual help, equality and brotherhood, justice, and love for the motherland which are conveyed to the goal. learning and learning materials. 2) The implementation stage in PPKn learning is carried out by approaching students by introducing cultural diversity, race, custom, and religion owned by students associated with the students' living environment themselves and inserting multicultural education values, namely inclusive values (open), tolerance , please help, equality and brotherhood, justice, and love for the motherland. 3) Evaluation of Civics learning that integrates multicultural education values is carried out by providing question points that have been answered by students and given an assessment by the teacher according to the level of accuracy and ability of all students.